The Effect of Artificial Intelligence Utilizing in Social Media Marketing - Yeyen Pratika (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
The development of Artificial Intelligence (AI) provides many opportunities in the current business structure. AI is used in various industries with different purposes, including creating engagement with customers. Financial technology (fintech) companies also utilize AI for giving product recommendations or targeted ads based on customers’ algorithms. Thus, this study aims to examine whether the use of AI in social media marketing can encourage consumers’ intention to use the products or services offered by the fintech companies. A total of 121 respondents were involved in this study with Structural Equation Modeling (SEM) as the analysis method. The result indicates that performance expectancy, utilitarian motivation and perceived valur co-creation influence the intention to invest.